Strategi Pengembangan Keberagamaan Mahasiswa Di Universitas Islam Negeri Sunan Gunung Djati Bandung Melalui Praktik Tilawah - Setiani, Annisa Isna; Laili, Nur; Abimanto, Dhanan (CV. Creative Tugu Pena, 2020)
The purpose of this study described the strategy of developing the diversity of Universitas Islam Negeri Gunung Djati Bandung through recitation practices and worship practices. This study used a field research, with qualitative research types. The research was intended to identify a number of facts or phenomena about the strategy of developing the diversity of Universitas Islam Negeri Gunung Djati Bandung through the practice of recitation and worship practices. Data collection techniques using observation. The collected data was interpreted and analyzed by reducing data, presenting data, and drawing conclusions. The results showed that the religious development strategy of the Universitas Islam Negeri Gunung Djati Bandung through tilawati practices and practices of worship is by (1) Creation of religious atmosphere such as greetings and handshakes, morning Qur'an, duha prayer, dzuhur prayer in congregation, PHBI, pesantren ramadhan , halal bi halal, qurban training, social service Keywords: Development Strategy, diversity, religious culture, Islamic character